PRESENTASI ESTETIS JARANAN SENTEREWE KOMUNITAS MANUNGGAL REKSO BUDOYO DALAM FESTIVAL JARANAN TRENGGALEK TAHUN 2023 - Margareta, Sherly Hanggary; Wahyudiarto, Dwi (Institut Seni Indonesia Surakarta, 2025)
This study examines the aesthetic presentation of the Jaranan Senterewe performance by the Manunggal Rekso Budoyo community at the 2023 Trenggalek Jaranan Festival. The research aims to analyze both the structural form and aesthetic components of the performance, using Sumandiyo Hadi’s theory of performance form and Doris Humphrey’s theory of performance aesthetics (as translated by Sal Murgiyanto). Employing a qualitative research method, data were collected through observation, interviews, and literature review. The findings indicate that the Jaranan Senterewe performance comprises distinctive elements such as dominant movements of the hands, feet, and head influenced by East Javanese traditions; a rigging stage as the performance space; pelog-based musical accompaniment with gendhing lancaran and sampak patterns; and a thematic emphasis on struggle and heroism. The performance features a group dance format with 14 male dancers, traditional costumes, bold makeup, neutral lighting, and symbolic props including kuda kepang, whips, Celeng, and Barongan. The aesthetic structure includes four main components: (1) Design, encompassing spatial formations and temporal sequencing; (2) Dynamics, involving variations in movement and musical intensity; (3) Rhythm, marked by traditional patterns such as mungkus and midak; and (4) Motivation, structured into opening, main, and closing sections. This study concludes that Jaranan Senterewe is a performance rich in symbolic meaning and artistic expression, contributing to the cultural vibrancy of East Javanese traditional arts.